Influence of Lunar Periodicity on the Size Composition and Abundance of Penaeid Prawns in Stake Net - V.C., George; V., Vijayan; P., George Mathai; M.D., Varghese; H., Krishna Iyer (Fishery Technology, 2025)
Data on length frequency of penaeid prawns landed by stake nets during lunar periods were analysed to assess variations in size composition and seasonal abundance. The full moon phase had lower size range compared to new moon phase and except in the case of P. indicus, the variation in catch between the two periods was not significant. In the case of M. dobsoni and M. monoceros, significant variation at 1% level was noticed between months.